THE RELATIONSHIP BETWEEN MATERNAL AGE AND PARITY ON THE INCIDENCE OF PREMATURE RUPTURE OF MEMBRANES - Wa Ode Sitti Fidia Husuni; Andi Sri Hastuti Handayani Usman; Nuraisyah Bahar (International Journal of Medicine and Health, 2022)
Premature rupture of membranes (PROM) is defined as the rupture of the membranes before the time of delivery at aterm pregnancy. The research used a quantitative study and an analytical survey with a Cross Sectional approach. The independent variable was parity and maternal age, while the dependent variable was premature rupture of membranes. This study used secondary data from 2019 to 2020. The population of this study were all 379 mothers giving birth in the VK room at the Muna Barat Hospital, and the sample in this study was 36 respondents who experienced PROM. The sample collection technique used a simple random sampling technique. This analysis used a contingency coefficient with an error rate (α = 0.05). The results showed that at term pregnancy there were 66% of mothers who experienced PROM in the age group < 20 years and > 35 years and at term pregnancy there were 71% experiencing PROM in the primipara and grandemultipara groups. From the results of statistical analysis were using SPSS, it was found that the P value < 0.05 for the age and parity groups, where these results indicated there is a relationship between maternal age (< 20 and > 35 years) and maternal parity (primipara and grade multipara) with the incidence of PROM. It is hoped that midwives as health service providers for pregnant, maternity and postpartum women can further enhance their role in providing counseling to women, both adolescents and women of childbearing age, about a safe reproductive age for pregnancy and childbirth.